(u-39)+u=u+35

Simple and best practice solution for (u-39)+u=u+35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (u-39)+u=u+35 equation:



(u-39)+u=u+35
We move all terms to the left:
(u-39)+u-(u+35)=0
We add all the numbers together, and all the variables
u+(u-39)-(u+35)=0
We get rid of parentheses
u+u-u-39-35=0
We add all the numbers together, and all the variables
u-74=0
We move all terms containing u to the left, all other terms to the right
u=74

See similar equations:

| 2x+1+x+3=90 | | x-3^1/2=8 | | 8=4x+19 | | x-31/2=8 | | 3^x-1=729^x/2 | | -3(y+3)=2y+1 | | 5-2|2x-2|=-5 | | 5/2p-7/6=1/2 | | 4(w+3)+7w=-9 | | 12c-15=45 | | 2.7=72.9/x | | 8d+10=90 | | (5d+1)^2=256 | | 191/2+2x=271/2 | | 12(x+10)=²4 | | /1/3(6x+9)=x-5 | | 45-2x=13 | | 3x2-3x=2x2+12x | | 5p+1=181 | | y=+4-1+18 | | 2.5-m=2.5 | | -2+x/5=7 | | 6.4=t/8.5 | | 4=w/2-4 | | 12^(2x-10)=1 | | 1=6+5x | | 1=6+x | | 4(x-3)-4(x+2)=7(3x-1)+29 | | g/2+11=23 | | x^2-8x=180 | | 6z+2=5z | | 8w-17=55 |

Equations solver categories